Kelayakan Hiasan Kepala (Headpiece) dari Limbah Plastik Jenis Kresek (Beauty and Beauty Health Education, 2023)
Abstract. Waste is leftover or discarded material resulting from an activity or production process on a household, industrial, and so on scale. Plastic bags are commonly used as a practical packaging tool at a low price and are included in the type of thermoplastic plastic that can be recycled to reduce potential environmental pollution. Researchers took the initiative to use plastic waste as a headdress (headpiece). The purpose of this study was to determine the feasibility of plastic waste as a basic material for making headpiece products through sensory tests and preference tests. The objects of this study were combs (P1), hairpins (P2), headbands (P3) and bobby pins (P4). The research subjects consisted of 3 expert judgments as product validators and sensory test assessments. Meanwhile, the preference test used 15 somewhat trained panelists in the field of makeup and hairdo. Data collection techniques using observation and documentation. Data analysis using descriptive percentage. Based on the product validity test assessment, it shows that the overall product is stated to be very valid with an average of 87%. The sensory test assessment results obtained an average of 93% with very good criteria. As for the assessment of the liking test, an average of 86% is included in the very like criteria. This proves that plastic bags have the potential to be reprocessed and exploratively optimized to become the main raw material for an aesthetic product. Keywords : waste, crackle, headdress (headpiece) Abstrak. Limbah adalah bahan sisa atau buangan yang dihasilkan dari suatu kegiatan atau proses produksi pada skala rumah tangga, industri, dan sebagainya. Plastik jenis kresek biasa digunakan sebagai alat pengemas praktis dengan harga murah dan termasuk dalam jenis plastik termoplastik yang dapat didaur ulang untuk mengurangi potensi pencemaran lingkungan. Limbah kresek dimanfaatkan sebagai hiasan kepala (headpiece). Tujuan penelitian ini adalah untuk mengetahui kelayakan limbah kresek sebagai bahan dasar pembuatan produk headpiece melalui uji inderawi dan uji kesukaan. Objek penelitian ini adalah sirkam (P1), hairpin (P2), headband (P3) dan bobby pin (P4). Subjek penelitian terdiri dari 3 expert judgment sebagai validator produk dan penilaian uji inderawi. Penilaian uji kesukaan menggunakan 15 panelis agak terlatih pada bidang makeup dan hairdo. Teknik pengumpulan data menggunakan observasi dan dokumentasi. Analisis data menggunakan deskriptif presentase. Berdasarkan penilaian uji validitas produk menunjukan bahwa keseluruhan produk dinyatakan sangat valid dengan rata-rata 87%. Hasil penilaian uji inderawi memperoleh rata-rata 93% dengan kriteria sangat baik. Penilaian uji kesukaan memperoleh rata-rata 86% termasuk dalam kriteria sangat suka. Hal tersebut membuktikan bahwa kresek berpotensi untuk diolah kembali dan dioptimalkan secara eksploratif menjadi bahan baku utama sebuah produk yang estetis. Kata kunci : limbah, kresek, hiasan kepala (headpiece)